Factors associated with medication nonadherence among hypertensives in Ghana and Nigeria (2015)
Background. Blood pressure (BP) control is poor among hypertensives in many parts of sub-Saharan Africa. A potentially modifiable factor for control of BP is medication non-adherence (MNA); our study therefore aimed to determine factors associated withMNA among hypertensives in Ghana and Nigeria. Methodology. We conducted a multicenter cross-sectional study. Patients were recruited from Korle-Bu Hospital (𝑛 = 120), Ghana; and University of Port Harcourt Teaching Hospital, (𝑛 = 73) Apapa General Hospital Lagos (𝑛 = 79) and University College Hospital Ibadan (𝑛 = 85), Nigeria. Results. 357 hypertensive patients (42.6% males) participated. MNA was found in 66.7%. Adherence showed correlation with depression (𝑟 = −0.208, 𝑃 < 0.001), concern about medications (𝑟 = −0.0347, 𝑃 = 0.002), and knowledge of hypertension (𝑟 = 0.14, 𝑃 = 0.006). MNA was associated with formal education (𝑃 = 0.001) and use of herbal preparation (𝑃 = 0.014). MNA was found in 61.7% of uninsured participants versus 73.1% of insured participants (𝑃 = 0.032). Poor BP control was observed in 69.7% and there was significant association between MNA and poor BP control (𝑃 = 0.006). Conclusion. MNA is high among hypertensives in Ghana and Nigeria and is associated with depression, concern about hypertensive medications, formal education, and use of herbal preparations. The negative association between health insurance and MNA suggests interplay of other factors and needs further investigation.